2011
DOI: 10.1016/j.neuropharm.2010.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition alters histone methylation associated with heat shock protein 70 promoter modifications in astrocytes and neurons

Abstract: The mood-stabilizing and anticonvulsant drug valproic acid (VPA) inhibits histone deacetylases (HDACs). The aim of the present study was to determine the effect of HDAC inhibition on overall and target gene promoter-associated histone methylation in rat cortical neurons and astrocytes. We found that VPA and other HDAC inhibitors, including sodium butyrate (SB), trichostatin A (TSA), and the Class I HDAC inhibitors MS-275 and apicidin all increased levels of histone 3 lysine 4 dimethylation and trimethylation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 43 publications
2
60
0
4
Order By: Relevance
“…Such permanent alterations are thought to be due to epigenetic changes at gene-specific promoter regions. Histone deacetylase inhibitors are now used as anticancer or anticonvulsive drugs but can lead to unintended alterations in the methylation of histones in a variety of tissues (33)(34)(35). Furthermore, the metabolic memory hypothesis presupposes that once a pattern of histone methylation is reset by stress, that pattern is maintained or replicated.…”
Section: Discussionmentioning
confidence: 99%
“…Such permanent alterations are thought to be due to epigenetic changes at gene-specific promoter regions. Histone deacetylase inhibitors are now used as anticancer or anticonvulsive drugs but can lead to unintended alterations in the methylation of histones in a variety of tissues (33)(34)(35). Furthermore, the metabolic memory hypothesis presupposes that once a pattern of histone methylation is reset by stress, that pattern is maintained or replicated.…”
Section: Discussionmentioning
confidence: 99%
“…The induction is further reflected on the level of histone methylation with increased H3K4 methylation at the HSP70 promoter of neurons as well as astrocytes. 77 The crucial role of HSP70 is confirmed by studies that show that HSP70 overexpression alone attenuates ischemic damage and seizures. [109][110][111] Interestingly, not only the histones at their expected location in the nucleus of the cell are involved in poststroke apoptotic processes.…”
Section: Excitotoxicitymentioning
confidence: 93%
“…76,77 Pan-HDACi, as well as Class I HDACi, increase histone 3 lysine 4 (H3K4) di-and trimethylation (me2/me3), which constitute typical marks of transcriptional activation. This may be accompanied by a decrease in repressive H3K9me2 levels.…”
Section: Epigenetic Mechanisms S Schweizer Et Almentioning
confidence: 99%
“…Moreover, beta-hydroxybutyate, an endogenous and specific inhibitor of class I HDACs (Shimazu et al, 2012), has been reported to protect primary rat mesencephalic neurons from 1-methyl-4-phenylpyridinium [MPP(+)]-induced toxicity (Kashiwaya et al, 2000). Another study reported regulation of heat shock protein 70 (Hsp70) expression through changes to the di-and trimethylation of histone H3 lysine 4 (H3K4me2 and H3K4me3) and p300 (HAT) recruitment (Marinova et al, 2009;Marinova et al, 2011;Leng et al, 2010). As a member of the heat shock protein family, Hsp70 is involved in protein folding, is able to upregulate the apoptotic regulator Bcl2, and is involved in several additional anti-apoptotic mechanisms (Yenari et al, 2005).…”
Section: Using Epigenetic Regulation To Promote Mdda Neuron Survivalmentioning
confidence: 99%